Kepemimpinan Kiai Tatang Isakandar dalam Mengembangkan Pondok Pesantren Raudatul Falah - Nurdin Nurdin; Ahmad Sarbini; Yuliani Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2020)
Penelitian ini bertujuan untuk mengetahui tipe kepemimpinan, cara pengambilan keputusan dan hubungan pemimpin terhadap santri dan lingkungan masyarakat, yang diterapkan K. Tatang Iskandar dalam mengembangkan Pondok Pesantren Raudatul Falah. Penelitian ini menggunakan metode penelitian deskriptif-kualitatif. Teknik pengumpulan data dilakukan melalui observasi dan wawancara mendalam. Analisis data dilakukan melalui interprestasi dan dihubungkan dengan konteks empiris pemimpin Pondok Pesantren Raudatul Falah. Hasil data penelitian menunjukkan bahwa tipe pimpinan Kiai Tatang Iskandar dalam mengembangkan Pondok Pesantren Raudatul Falah adalah kepemimpinan Demokratis dan Karismatik. Hal tersebut dapat dilihat dari cara beliau dalam pengambilan keputusan yang selalu menggunakan kebersamaan, musyawarah untuk mencapai kata mufakat. Kepemimpinan Kiai Tatang Iskandar sangat menjadi panutan yang baik bagi seorang pemimpin, itu terbukti dengan keberadaan Pondok Pesantren Raudatul Falah yang sampai saat ini masih berdiri kokoh di lingkungan masyarakat. ABSTRACT This research is in accordance with the idea that to achieve certain goals, cooperation between management and leaders is needed. In this case the leader is very significant to achieve these goals. This leadership includes coordination, organizing and controlling members who determine goals and directions to achieve fulfilling goals to carry out activities and connect with other activities, in addition, the leader is also a direction set, an effective, rational, objective and effective communicator. neutral . This research uses descriptive-qualitative research methods. The research steps taken include; Determination of research locations, research methods, determination of data types, collection of data types, data observation is done through observation and in-depth interviews. Data analysis was carried out through interpretation and related to the empirical context of the leader of the Raudatul Falah Islamic Boarding School. The results of the research data indicate that the leadership of Kiai Tatang Iskandar in developing the Raudatul Falah Islamic Boarding School is Democratic and Charismatic leadership. This can be seen from the way in which decisions always use togetherness, deliberation to reach a consensus. The leadership of Kiai Tatang Iskandar is a very good role model for a leader, it is proven by the existence of the Raudatul Falah Islamic Boarding School which is still standing firmly in the community.